2006
DOI: 10.1089/vim.2006.19.481
|View full text |Cite
|
Sign up to set email alerts
|

In VivoExpression of Immunosuppressive Cytokines in Human Papillomavirus-Transformed Cervical Cancer Cells

Abstract: Genital human Papillomavirus infection is common and only a minor fraction of infected subjects develop progressing cervical epithelial lesions or cancer. Bypassing local immune responses is important for the development of cervical cancer. In this work we determined the cytokine pattern in samples from patients with cervical cancer. Thus, we examined the local mRNA expression profile of helper T cell type 1 (Th1), Th2, and Th3 cytokines in HPV-positive cervical cancer biopsies by reverse transcription-polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 44 publications
8
80
0
3
Order By: Relevance
“…Factors secreted by tumor cells that have been implicated in the prevention or modulation of DC differentiation and/or function are VEGF, macrophage colony-stimulating factor (M-CSF), TGF (TGF-b1), IL-10, IL-6, and prostanoids (e.g., PGE 2 ) (12). CxCas are known also to secrete immunomodulatory compounds, but their effect on APCs is yet unknown (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Factors secreted by tumor cells that have been implicated in the prevention or modulation of DC differentiation and/or function are VEGF, macrophage colony-stimulating factor (M-CSF), TGF (TGF-b1), IL-10, IL-6, and prostanoids (e.g., PGE 2 ) (12). CxCas are known also to secrete immunomodulatory compounds, but their effect on APCs is yet unknown (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Previously, we demonstrated that HPV infection induces il-10 expression in patients with cervical cancer (26). in addition, an HPV e2 recognition site in the position from -2,203 to -2,191 nt in the human il-10 promoter has been reported (18).…”
Section: Resultsmentioning
confidence: 92%
“…in other cases, il-10 is produced by activated cells involved in the host antitumor response; thus il-10 may be an indicator of a potent inflammatory response rather than immunosuppression. in particular, it has been found that il-10 is highly expressed locally in biopsies from patients with premalignant lesions and cervical cancer, and may induce a local immunosuppressive state (5,26,29,30). Thus, elucidating the mechanisms of il-10 gene expression during cervical cancer development may aid in the understanding of il-10 function in the context of the antitumor immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pro-tumor immune activities are mediated by molecules like cytokines, chemokines, myeloid suppressor cells, and Treg or regulatory T-cells [17] . Tumor derived cytokine and chemokine signals neutralize the immune effector cells, which may be mediated by NF-κB pathway [18,19] . Surface antigens in tumor cells are tumor specific, and this characteristic has been targeted effectively at clinical level by tumor antigen specific monoclonal antibodies like rituximab, trastuzumab and cetuximab [20] .…”
Section: Tumor Microenvironment and Immune Systemmentioning
confidence: 99%